Pengaruh Efek Sisaan Eco Enzyme dan Pupuk Kandang Ayam terhadap Pertumbuhan dan Produksi Selada - Elisabeth Sri Pujiastuti; Yanto Raya Tampubolon; Susana Tabah Trina; Juli Ritha Tarigan; Ferlist Rio Siahaan (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
A study consisted of two growing seasons of lettuce was held to observe the residual effect of eco enzyme and chicken manure on the growth and yield of lettuce on the second growing season. The research was held in Medan and was done using factorial randomized block design, with two treatments and three replications. The first factor was the concentration of eco enzyme, with three levels of 0, 1 and 2 ml/L. The second one was the dose of chicken manure, with three levels of 0, 15 and 30 tons/hectare. The application of the eco enzyme and chicken manure was done only on the first growing season. The parameters were: number of leaves, root volume, fresh weight and the total yield of lettuce. The result showed that there was a residual effect of eco enzyme and chicken manure application on the growth and production of lettuce. The concentration of eco enzyme had a very significant effect on the number of leaves at 14 DAP, but there was no significant effect on other parameters. The relationship between eco enzyme concentration and the number of leaves at 14 DAP was linear. The dose of chicken manure had a very significant effect on all variables at each time of observation. The relationship between the dose of chicken manure and the number of leaves at 14, 21 and 35 DAP, the fresh and total yield was also linear. The relationship between the dose of chicken manure and the number of leaves at 28 DAP and the root volume was quadratic, with the optimum doses of chicken manure were: 27.05 and 22.5 tons/ha, respectively. No interaction was observed between the concentration of eco enzyme and the dose of chicken manure on all variables at each time of observation.